Factors Affecting Smoking Menthol Brand Cigarette Among The Adult Population In Sarawak, Malaysia - Md Mizanur Rahman,; Mohd Taha Arif,; Mohd Fadzillah Abd Razak,; Mohd Raili bin Suhaili,; Zainab Tambi,; Cliffton Akoi; Deburra Peak Ngadan (Malaysian Public Health Physicians' Association, 2024)
Menthol brand cigarette has been found to be linked with early initiation of smoking and addiction of nicotine. This study was designed to find out the factors associated with smoking menthol brand cigarettes among adult population in Sarawak. This was a cross-sectional study conducted among the adult population in Sarawak. Data were collected from ten villages in Kota Samarahan and Kuching Division by face to face interview using modified Global Adult Tobacco Survey questionnaire. Non-probability purposive sampling method was adopted to select the villages. All the households of the villages were visited, and an adult member was selected randomly from each household irrespective of sex. After missing value imputation, 1000 data sets were analysed using statistical software SPSS 19.0 version. Analysis showed that 28.8% of the respondents were current smokers, and 7.8% were past smokers. Among the smokers, 56.3% were habituated with menthol brand cigarette. Logistic regression analysis revealed that age at initiation of smoking before 15 years of age (OR=11. 68, 95% CI: 4.25, 32.10), smoking within five minutes of wake up from sleep (OR=3. 20, 95% CI: 1.35, 7.54), nature of job as business (OR=4. 81, 95% CI: 2.13, 10.86) and service holders (OR= 3.85, 95% CI: 2.07, 7.16) and family size 5 and above (OR=2. 22, 95% CI: 1.25, 3.94) appeared to be important determinants of smoking any menthol brand cigarette (p<0.05). Menthol is a prominent design feature to attract and retain younger smokers. It does not necessarily make the transition from experimenting with cigarettes, but to encourage early smokers to become a confirmed smoker. So, anti-tobacco public health programme should focus on age-specific community approach.